2021
DOI: 10.3390/ijerph182413049
|View full text |Cite
|
Sign up to set email alerts
|

Temporal–Spatial Evolution and Influencing Factors of Coordinated Development of the Population, Resources, Economy and Environment (PREE) System: Evidence from 31 Provinces in China

Abstract: Facing the increasingly severe friction among the domains of population, resources, economy and environment (PREE) in a system, theoretical guidance for the sustainable development of a PREE system can be obtained by exploring the coordinated development of a PREE system during its temporal–spatial evolution process. Based on the PREE data of 31 provinces in China from 2010 to 2019, this study uses a spatial measurement method to analyze the temporal and spatial evolution characteristics of the PREE systems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Our research findings reveal a step-like pattern of "higher in the southeast and lower in the northwest" in the spatial distribution of the coupling coordination degree between new urbanization and rural revitalization. This pattern aligns with the results of Cao J. et al (2021) [49], further confirming the close relationship between the coupling coordination degree of new urbanization and rural revitalization and regional population, economy, and resources. Additionally, this study further explored several factors influencing the coupling coordination degree, among which the factor of innovation environment played a dominant role.…”
Section: Relevance To Existing Researchsupporting
confidence: 90%
“…Our research findings reveal a step-like pattern of "higher in the southeast and lower in the northwest" in the spatial distribution of the coupling coordination degree between new urbanization and rural revitalization. This pattern aligns with the results of Cao J. et al (2021) [49], further confirming the close relationship between the coupling coordination degree of new urbanization and rural revitalization and regional population, economy, and resources. Additionally, this study further explored several factors influencing the coupling coordination degree, among which the factor of innovation environment played a dominant role.…”
Section: Relevance To Existing Researchsupporting
confidence: 90%
“…The coupling coordination degree of new-type urbanization and ecological environment was divided into 10 types [25], as shown in Table 1. The coefficient of variation (Cv), also known as the "standard deviation rate", is a statistic that measures the degree of variation of the observed value, and reflects the degree of dispersion on the unit mean [26]. The global test of the coefficient of variation is calculated by Cv = S/ X (10) where S is the standard deviation of a sample and X is the mean of the sample.…”
Section: Coupling Coordination Degree Modelmentioning
confidence: 99%
“…With improvements to China's comprehensive national strength, China will inevitably promote high-quality development strategies to realize the coordinated development of pseudo and real human settlements in specific regions and across the entire country. Previous research has shown that (Cao et al, 2021;Wang et al, 2021a), due to the implementation and promotion of strategies for developing the western region, revitalizing the northeast, and coordinating the development of Beijing, Tianjin, and Hebei, the coordination degree of development in various parts of China has been characterized by an upward trend. However, overall, considerable opportunities remain for development.…”
Section: Discussionmentioning
confidence: 99%